A new method of evaluating interfacial properties of a fiber/matrix composite. (February 2015) - Budiman, Bentang Arief; Takahashi, Kosuke; Inaba, Kazuaki; Kishimoto, Kikuo
Interfacial debonding frequently initiates composite failure in a fiber/matrix composite. A single-fiber fragmentation test and its modifications can be used to evaluate interfacial properties. However, they still have accuracy problems due to fiber impurities and friction work. This paper presents a new method of evaluating interfacial properties using a stress contour of composite matrix. A single-fiber fragmentation test model was developed to simulate the stress contour. The interface was modeled as a cohesive zone model. Four characteristic lengths on the stress contour were found after conducting simulations with many interfacial properties values. The stress contour was then captured from the single-fiber fragmentation test employing a photo-elasticity technique and the four characteristic lengths were measured. Iteration in simulation involved changing interfacial properties until corresponding characteristic lengths from experiment and simulation were obtained. The results were compared with those obtained with existing methods and found to be reasonable.